The bank lending channel of monetary policy: identification and estimation using Portuguese micro bank data - Luísa Farinha; Carlos Robalo Marques (European Central Bank (ECB), 2001)
This paper investigates the existence of the bank-lending channel in the transmission of monetary policy using Portuguese micro bank data. In contrast to the conventional approach, which addresses the identification issue by resorting to reduced form equations for bank credit with variables in differences, we directly estimate loan-supply schedules with variables in levels, thereby exploiting recent results on cointegration for panel data. We conclude that there is evidence of the existence of a bank-lending channel, and that the importance of the bank lending-channel is larger for less capitalised banks
Keywords: C33; E44; E52; G21; 330; bank lending channel; Identification; Monetary policy transmission mechanism